2020
DOI: 10.1016/j.redox.2019.101411
|View full text |Cite
|
Sign up to set email alerts
|

Salusin-β mediates tubular cell apoptosis in acute kidney injury: Involvement of the PKC/ROS signaling pathway

Abstract: Salusin-β is abundantly expressed in many organs and tissues including heart, blood vessels, brain and kidneys. Recent studies have identified salusin-β as a bioactive peptide that contributes to various diseases, such as atherosclerosis, hypertension, diabetes and metabolic syndrome. However, the role of salusin-β in the pathogenesis of acute kidney injury (AKI) is largely unclear. In the present study, we investigated the roles of salusin-β in cisplatin or lipopolysaccharide (LPS)-induced renal injury. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 90 publications
2
34
0
Order By: Relevance
“…Moreover, the therapeutic effects of polysulfide and H 2 S on cisplatin-induced inflammation response were also assessed in mice as inflammation is critically involved in the pathologies of cisplatin nephrotoxicity [ 27 ]. As previously described [ 28 , 29 ], the levels of TNF-α and IL-1β in both serum and renal tissues were significantly enhanced in cisplatin-induced mice, and these upregulated pro-inflammatory cytokines were diminished by Na 2 S 4 , NaHS, and GYY4137 ( Figure 5 A–B). Then, we conducted RT-PCR and immunoblot to testify the expressions of pro-inflammatory cytokines in renal tissues, including TNF-α, IL-1β, IL-6, and COX-2.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, the therapeutic effects of polysulfide and H 2 S on cisplatin-induced inflammation response were also assessed in mice as inflammation is critically involved in the pathologies of cisplatin nephrotoxicity [ 27 ]. As previously described [ 28 , 29 ], the levels of TNF-α and IL-1β in both serum and renal tissues were significantly enhanced in cisplatin-induced mice, and these upregulated pro-inflammatory cytokines were diminished by Na 2 S 4 , NaHS, and GYY4137 ( Figure 5 A–B). Then, we conducted RT-PCR and immunoblot to testify the expressions of pro-inflammatory cytokines in renal tissues, including TNF-α, IL-1β, IL-6, and COX-2.…”
Section: Resultssupporting
confidence: 78%
“…At the end of animal experiments, the serum samples were collected and the serum BUN and creatinine levels were measured to evaluate kidney function by using commercially available kits (Nanjing Jiancheng Bioengineering Institute, Nanjing, China) in accordance with the manufacturer’s protocols [ 29 , 75 ]. The absorbance for serum BUN was analyzed at 640 nm by a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the enhanced oxidative stress is predominantly regulated by various NADPH oxidases (NOX) isoforms, including p22 phox , p47 phox and NOX2 in diabetic nephropathy [ 57 ]. The membrane translocation of p47 phox is a fundamental event for the formation of reactive oxygen species (ROS) in both diabetic kidney disease and acute kidney injury [ 58 , 59 ]. In comparison with NG-treated cells, the protein expression levels of p22 phox , p47 phox and NOX2 were augmented in HK-2 cells upon exposure to HG, and this effect was counteracted by preconditioning with Na 2 S 4 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 17 Indeed, salusin-β knockdown reduced cell proliferation, apoptosis, oxidative stress, and inflammation in cisplatin- or LPS-induced renal tubular cells and mice with acute kidney injury; however, salusin-β overexpression reversed these effects. 18 Additionally, another study indicated that salusin-β silencing reduced high glucose (HG)-induced apoptosis by upregulating Bcl-2 expression and downregulating Bax and caspase-3 expression in human umbilical vein endothelial cells. 17 Moreover, other studies revealed that salusin-β blockade alleviated oxidative stress, inflammation, and cardiac dysfunction in diabetic rats.…”
Section: Introductionmentioning
confidence: 99%